Growth performance, physiological parameters, and transcript levels of lipid metabolism-related genes in hybrid yellow catfish (Tachysurus fulvidraco ♀ × Pseudobagrus vachellii ♂) fed diets containing Siberian ginseng - Li, Ming Xiao (PLoS One, 2021)
In high-density aquaculture, fish health can suffer because of excessive feeding, which causes fatty liver disease. Siberian ginseng (Acanthopanax senticosus) has been used as a feed additive to promote animal growth, immunity, and lipid metabolism. In this study, we explored the effects of A. senticosus on the physiology of hybrid yellow catfish (Tachysurus fulvidraco ♀ × Pseudobagrus vachellii ♂). A control group and five groups fed diets containing A. senticosus (0.5, 1, 2, 4, and 8 g A. senticosus/kg feed) were established and maintained for 8 weeks. Dietary supplementation with A. senticosus at 4 g/kg promoted growth of the hybrid yellow catfish. Serum total cholesterol (TC) and triacylglycerol (TG) levels at 2 g/kg A. senticosus (TC: 1.31 mmol/L; TG: 1.08 mmol/L) were significantly lower than in the control group (TC: 1.51 mmol/L; TG: 1.41 mmol/L), and 4 g/kg A. senticosus (17.20 μmol/g tissue) reduced the liver TG level compared with the control group (21.36 μmol/g tissue) (P <0.05). Comparative transcriptomic analysis of liver tissue between the control group and the group showing optimum growth (4 g/kg A. senticosus) revealed 820 differentially expressed genes and 44 significantly enriched pathways, especially lipid metabolism pathways such as unsaturated fatty acid and fatty acid metabolism. The transcript levels of five lipid metabolism-related genes were determined by quantitative real-time PCR. The results showed that 2–4 g/kg A. senticosus supplementation reduced the FADS2, ELOVL2, CYP24a, and PLPP3 transcript levels and 4 g/kg A. senticosus increased the DIO2 transcript level (P <0.05), leading to altered synthesis of TG and thyroxine and reduced fat deposition in the liver. Our results show that dietary A. senticosus affects the regulation of fat metabolism and promotes the growth of hybrid yellow catfish. A. senticosus is a healthy feed additive, and the appropriate dietary supplementation rate is 2–4 g/kg.